2008
DOI: 10.1007/s00405-008-0821-7
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmic disturbances in children with sensorineural hearing loss

Abstract: Co-incidence of sensorineural hearing loss and ophthalmic abnormalities has a tremendous influence on development of children. This study was done to determine the nature and prevalence of ophthalmic disturbances in children with congenital sensorineural hearing loss. In a descriptive cross-sectional study, complete ophthalmologic examinations such as assessment of visual acuity, cycloplegic refraction, ocular motility examination, slit lamp examination and indirect funduscopy on 50 children with sensorineural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 8 publications
2
12
1
2
Order By: Relevance
“…A study by Bakhshaee et al 6 also showed that refractive errors were the most common ocular problems in children with sensorineural hearing loss. Another study on Iranian children also reported that about 40% of the deaf students suffered from refractive errors.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…A study by Bakhshaee et al 6 also showed that refractive errors were the most common ocular problems in children with sensorineural hearing loss. Another study on Iranian children also reported that about 40% of the deaf students suffered from refractive errors.…”
Section: Discussionmentioning
confidence: 96%
“…4 , 7 , 9 , 10 Nevertheless, the condition of refractive errors in this population compared to the normal population cannot be judged because the majority of studies were descriptive and did not have a control group. 6 , 11 Previous studies confirm that refractive errors are the most prevalent visual disorder in not only deaf children but also the older deaf population. 6 , 11…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations